Quantitation of in vitro opsonic activity of human antibody induced by a vaccine consisting of the type III-specific polysaccharide of group B streptococcus. - De Cueninck, B J (1983)
Human antibody, induced by a vaccine consisting of undegraded and highly purified extracellular type III-specific polysaccharide of group B streptococcus, was shown to increase the rate of phagocyte-mediated killing of bacteria of the homologous type. The bactericidal effect was mediated by type III-specific antibody and was complement dependent. An assay which permitted quantitation of "opsonic activity" was developed. In this assay, loss of CFUs occurred at a constant rate, and the rate constant was used as a measure of opsonic activity of antisera. A linear relationship between type III-specific antibody concentration (40 to 500 ng/ml) and the rate constant of killing was observed. When sets of immune sera were tested, some sera reacted anomalously, mediating significantly higher or lower rates than expected on the basis of their antibody content. Since type III-specific antibody in immune sera was found almost exclusively in the immunoglobulin G class, we hypothesize that differences in immunoglobulin G subclass distribution of specific antibody may have been the source of this variation.